Gingivitis in children and adolescents: epidemiological overview and associated factors—A narrative review - Elgasmi, Fatima Ezzahra; Maghous, Kenza; Badre, Bouchra (Frontiers in Oral Health, 2025)
BackgroundGingivitis is the most prevalent periodontal disease in children and adolescents. Although reversible, its high prevalence highlights a significant public health concern, especially in underserved populations.MethodsA narrative literature review was conducted using PubMed, Scopus, and Google Scholar to identify English and French studies published between 2014 and 2024. Inclusion criteria focused on epidemiological studies reporting prevalence, risk factors, and preventive strategies of gingivitis in pediatric populations.ResultsGingivitis prevalence among children and adolescents varies widely across countries, ranging from 20% to over 90%. Higher rates were observed in socioeconomically disadvantaged populations. Key risk factors include poor oral hygiene, sugar-rich diets, low parental education, orthodontic appliances, and limited access to preventive care.ConclusionGingivitis in pediatric populations remains a global concern. Multilevel strategies involving families, schools, and oral health professionals are essential to improve prevention, health education, and access to care in order to reduce disease burden.